A Marketing Work-Integrated-Learning Project: A working model - Wait, Marius (South African Journal of Higher Education, 2016)
The problem with WIL is that its benefits are undoubted, but difficult to substantiate. The informal and anecdotal evidence in favour of WIL is overwhelming, but the hurdles in the way of proper research are equally formidable (Sietsma 2004: 14). This paper is an example of a working Work Integrated Learning (WIL) project offered to students enrolled for the National Diploma: Marketing at the University of Johannesburg (UJ). This project is unique and has also won several awards. This project is a practical sales assignment attached to the theoretical subjects Personal Selling in the first year of study and Sales Management in the second year of study. Students are taught the academic textbook knowledge in class and are then expected to apply this knowledge in a real-life environment, by reaching a set sales target. The UJ has partnered with the Direct Selling Association in South Africa which controls this project from and industry perspective. The methodology followed was deductive content analysis of interviews with students who had passed the course. The result reflected a resounding successful project. Keywords – Practical selling project, direct selling, WIL.